------ ----- _ ------ --------
3-x 3-x x-3 x+3
Answer:0
Step-by-step explanation:
Q=-7a^2-3ab+5b^2
P-Q
Answer:
3a² + ab + 4b²
Step-by-step explanation:
Combine like terms. Like terms have same variable with same power.
P - Q = -4a² - 2ab + 9b² - (-7a² - 3ab + 5b²)
To open the brackets, multiply each term of Q by (-1)
= -4a² - 2ab + 9b² + 7a²+ 3ab - 5b²
-4a² and 7a² are like terms.
(-2ab) and 3ab are like terms.
9b² and (-5b²) are like terms.
= -4a² + 7a² -2ab + 3ab + 9b²- 5b²
= 3a² + ab + 4b²
Answer:
3a² + ab + 4b²
Step-by-step explanation:
P - Q
= - 4a² - 2ab + 9b² - (- 7a² - 3ab + 5b² ) ← distribute parenthesis by - 1
= - 4a² - 2ab + 9b² + 7a² + 3ab - 5b² ← collect like terms
= 3a² + ab + 4b²
Round your answer to the nearest tenth.
HELP PLEASE
The required 6 kilometers in miles is given as 3.6 miles.
Given that,
To Value of 6 kilometers in miles is to be determined.
The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.
Here,
1 km = 0.6 mi,
multiply both sides by 6
6 km = 3.6 mi
Thus, the required 6 kilometers in miles is given as 3.6 miles.
Learn more about simplification here:
#SPJ1
b.2y + 3x = 10
c.2x + 3y = 10
b. 22
c. 24
d. 25
In the sequence 0, 3, 8, 15, a5, 35, the term a5 equals 24 as each term in the sequence is the square of its position minus 1.
To determine the value of a5 in the sequence 0, 3, 8, 15, a5, 35,... let's first analyze the pattern in the sequence. Each term equals the square of the term's position in the sequence minus 1. This implies that the first term is (1²-1)=0, the second term is (2²-1)=3, the third term is (3²-1)=8, and so on. Hence, the fifth term a5 would be (5²-1)=24. So, the answer is c. 24.
#SPJ2